2015
DOI: 10.1016/j.bbrc.2015.02.080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically stimulated bone cells secrete paracrine factors that regulate osteoprogenitor recruitment, proliferation, and differentiation

Abstract: ABSTRACT:Bone formation requires the recruitment, proliferation and osteogenic differentiation of mesenchymal progenitors. A potent stimulus driving this process is mechanical loading, yet the signalling mechanisms underpinning this are incompletely understood. The objective of this study was to investigate the role of the mechanically-stimulated osteocyte and osteoblast secretome in coordinating progenitor contributions to bone formation. Initially osteocytes (MLO-Y4) and osteoblasts (MC3T3) were mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 31 publications
(42 reference statements)
6
47
0
Order By: Relevance
“…Although the signaling mechanisms of load‐induced cell proliferation or activation remain unknown, it is well‐established that osteocytes are mechanosensor cells that play a role in the anabolic response to loading . Recent in vitro evidence indicates mechanically stimulated osteocytes secrete factors that stimulate osteoblast and mesenchymal progenitor cell migration and proliferation . Although our in vivo study did not investigate this phenomenon, it offers a possible mechanism for loading‐induced periosteal cell proliferation.…”
Section: Discussionmentioning
confidence: 72%
“…Although the signaling mechanisms of load‐induced cell proliferation or activation remain unknown, it is well‐established that osteocytes are mechanosensor cells that play a role in the anabolic response to loading . Recent in vitro evidence indicates mechanically stimulated osteocytes secrete factors that stimulate osteoblast and mesenchymal progenitor cell migration and proliferation . Although our in vivo study did not investigate this phenomenon, it offers a possible mechanism for loading‐induced periosteal cell proliferation.…”
Section: Discussionmentioning
confidence: 72%
“…We have performed PCR and Western blotting analyses for FGF23 expression, whereas no detectable FGF23 gene or protein expression was observed in MLO‐Y4 cells. Many previous studies have also reported that the expression levels of FGF23 in the MLO‐Y4 cell line were negligible/undetectable (Woo et al, ; Atkins et al, ; Sun et al, ; Brady et al, ), which represents an important limitation of the MLO‐Y4 cell line. OCN is an abundant noncollagenous component of the organic bone matrix secreted mainly by osteocytes and osteoblasts (Florencio‐Silva et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…We observed a decrease in loadinginduced periosteal activation in bone, where the cilium was deleted in the progenitor population and not the osteoblast, which suggests that loading-induced periosteal activation is caused by the recruitment and differentiation of osteogenic progenitors, not dormant osteoblasts. One potential mechanism for recruitment and differentiation is that osteocytes, previously thought to be essential in bone mechanotransduction (26), detect mechanical stimulation and then release paracrine signals, which are detected by progenitor cells (27)(28)(29). Recent work by our group has demonstrated that soluble factors secreted by mechanically stimulated osteocytes can significantly enhance MSC migration in vitro (28); however, an alternative mechanism may be that progenitor cells directly sense these biophysical signals.…”
Section: Discussionmentioning
confidence: 99%